A new ant species of the Leptogenys sulcinoda-group (Hymenoptera: Formicidae) from Saudi Arabia. Issue 1 (2nd January 2017) - Sharaf, Mostafa R.; Akbar, Shahid A.; Al Dhafer, Hathal M.; Aldawood, Abdulrahman S.
Abstract : Leptogenys polaszeki sp. n. is described from the Asir Mountains, Saudi Arabia, based on the worker caste. The new species is a member of the L. sulcinoda -group and appears closest to L. bellii Emery, 1901, originally described from Ethiopia. The likely male caste of L. polaszeki sp. n. is described based on a single specimen collected by a pitfall trap in the type locality. http://www.zoobank.org/urn:urn:lsid:zoobank.org:pub:5D3BF3AF-5308–48E8–8416–902278909AD5